An Ethnographic Study Of Islamic Educational Values In The 1 Muharram Ta’aruf Parade Tradition Among The Tegal Rejo Village Community - Anna Damayanti; Siska Wulandari; Jossiselfiah; Fitri Oviyanti; Maryamah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study explores the embodiment of Islamic educational values within the 1 Muharram Ta’aruf Parade tradition in Tegal Rejo Village, Indonesia. Employing a qualitative ethnographic approach, it investigates how Islamic values are expressed, transmitted, and internalized through this annual communal event. Data were obtained through participant observation, in-depth interviews, and documentation involving religious leaders, educators, and community members. The findings reveal that the Ta’aruf Parade embodies three core values of Islamic education: aqidah (faith), akhlaq (moral conduct), and ibadah (worship). These values are manifested through collective participation, cooperation, and symbolic performances that merge religious devotion with cultural expression. The study further demonstrates that this tradition represents a living model of ta’dīb the holistic cultivation of faith, morality, and spirituality through experiential and contextual learning. In conclusion, the 1 Muharram Ta’aruf Parade functions as a culturally rooted pedagogical system that reinforces Islamic values, strengthens social cohesion, and preserves cultural identity. It underscores the vital role of community-based traditions as effective educational media for sustaining moral and spiritual development in contemporary Muslim society.